The Department of Guidance and Counseling Students’ Learning Difficulties on Group Counseling Practicum in the Special Region of Yogyakarta - Sutanti, Tri; Suwarjo, Suwarjo; Handaka, Irvan Budhi; Astuti, Budi (Psikopedagogia, 2017)
This study aimed to discover the learning difficulties experienced by the guidance and counseling students on group counseling practicum. This study was categorized as a descriptive study involving 286 students of seven Universities in the Special Region of Yogyakarta as the sample of the study. The sample was taken by using purposive sampling technique. The data collection technique of this study was a learning difficulties in group counseling practicum questionnaire by open and closed-ended questions. The data of this study were analyzed by using simple descriptive analysis by calculating the percentage and the categorization of the questionnaire score. The result of the study showed that the most contributing factor to the the students’ learning difficulties on the group counseling practicum was the aspect of the lecturer' teaching method by 53.31%. Besides, the result of the open-ended questionnaire showed that lack of group counseling basic skill mastery is one of the difficulties they experience during the group counseling service at the school. It contributes 38.46%. It showed that the practicum teaching methods need improvement to optimize the students' ability in practicing group counseling in school. This study becomes the basic consideration of the needs of learning model for group counseling practicum for the students of guidance and counseling in the Special Region of Yogyakarta.